Association of NF-E2 Related Factor 2 (Nrf2) and inflammatory cytokines in recent onset Type 2 Diabetes Mellitus - Sireesh, Dornadula; Dhamodharan, Umapathy; Ezhilarasi, Krishnamoorthy; Vijay, Viswanathan; Ramkumar, Kunka Mohanram (Scientific reports, 2018)
We investigated the association of redox regulator Nuclear factor erythroid 2-related factor 2 (Nrf2) and inflammatory cytokines as well as clinical remission in patients with recent onset type 2 diabetes (DM). Blood was collected from 180 DM patients (105 males/75 females) and 150 control subjects (86 males/64 females). Blood glucose, HbA1c, lipid profile and Nrf2 levels were determined along with circulatory cytokines in study subjects. The data were adjusted with confounding factors such as age and sex using multiple logistic regression analysis. We found that Th1/Th2 and oxidative stress markers were significantly elevated, whereas Nrf2 and its downstream targets were decreased in peripheral blood mononuclear cells (PBMCs) of DM subjects when compared with control. The circulatory levels of Nrf2 showed a positive correlation with Th2 cytokines and negative correlation to Th1 cytokines. Further, the impaired insulin secretion in pancreatic β-cells observed due to cytokine stress has been restored by activation of Nrf2 as assessed by glucose-stimulated insulin secretion (GSIS). This study identifies Nrf2 plays a central role in skewing Th1 and Th2 dominance in the progression of diabetes.